2020
DOI: 10.2174/1874070702115010001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Garlic (Allium Sativum L.) to Intra-row Spacing and Variety at Selekeleka, Northern Ethiopia

Abstract: Background: Garlic is an important condiment and cash crop in Ethiopia. Low yield and productivity of the crop are the major characteristics of the crop in the country. Many factors affect the productivity of the crop in the country, however poor agronomic practices, especially the use of low-yielding varieties and inappropriate spacing, are the major ones. Objective: The aim of this study is to evaluate the growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 15 publications
1
27
3
Order By: Relevance
“…Several researchers had reported that genetic diversity in garlic is revealed in genotypes that are tested for a variety of different morphological (growth, yield, and yield traits) traits that indicate the presence of true variability in the garlic [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Azene [ 56 ] indicated that there was great variability among the garlic accessions for leaf length (cm), number of leaves per plant (cm), bulb weight (g), bulb diameter (equatorial) (cm), number of cloves per bulb, clove weight (g), and bulb yield (tons per hectare).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers had reported that genetic diversity in garlic is revealed in genotypes that are tested for a variety of different morphological (growth, yield, and yield traits) traits that indicate the presence of true variability in the garlic [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Azene [ 56 ] indicated that there was great variability among the garlic accessions for leaf length (cm), number of leaves per plant (cm), bulb weight (g), bulb diameter (equatorial) (cm), number of cloves per bulb, clove weight (g), and bulb yield (tons per hectare).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The total production from 12,429 ha of land was only 124,801 quartiles. The low production of garlic growth, yield, and yield-related traits was due to biotic and abiotic factors such as lack of high-yielding genotypes [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ], inappropriate organic and inorganic fertilizer [ 3 , 4 , 18 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ], inappropriate intra-row spacing [ 38 , 42 , 43 , [53] , [54] , [55] , [56] , 69 ], clove weight and size [ [57] , [58] , [59] , [60] ], watering [ [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ], mulching [ 70 , 71 ], disease [ 12 , 36 , 42 , [53] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations